1976
DOI: 10.1254/jjp.26.65
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between the Levels of Intracellular Cyclic Nucleotides and Mechanical Responses Induced by Drugs

Abstract: Abstract-The tracheal smooth muscle dissected free from connective tissues was used as a test preparation, since isoprenaline caused a decrease in cyclic GMP in the muscle while it caused an increase in cyclic GMP in the remaining tracheal tissue. Acetylcholine, histamine and papaverine increased both cyclic AMP and cyclic GMP levels in the tracheal muscle. Isoprenaline increased the cyclic AMP level but decreased the cyclic GMP level. However, when tracheal muscle was incubated with isoprenaline in the presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
11
0

Year Published

1978
1978
1995
1995

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 18 publications
3
11
0
Order By: Relevance
“…One piece was used for measuring the control level of cyclic AMP and the other for estimating any change of cyclic AMP concentration after treatment with the test drugs. The tissues were homogenized with a glass homogenizer in 2 ml of cold trichloroacetic acid (6% w/v) that contained 0.5 pmol of [3H]cyclic GMP to estimate the recovery of cyclic AMP (15). The homogenate was centrifuged at 3000 rpm at 01C for 15 min, the supernatant was then acidified with 1 N HC1, and the trichloroacetic acid was extracted with ether.…”
Section: Estimation Of Cyclic Amp Levelsmentioning
confidence: 99%
See 1 more Smart Citation
“…One piece was used for measuring the control level of cyclic AMP and the other for estimating any change of cyclic AMP concentration after treatment with the test drugs. The tissues were homogenized with a glass homogenizer in 2 ml of cold trichloroacetic acid (6% w/v) that contained 0.5 pmol of [3H]cyclic GMP to estimate the recovery of cyclic AMP (15). The homogenate was centrifuged at 3000 rpm at 01C for 15 min, the supernatant was then acidified with 1 N HC1, and the trichloroacetic acid was extracted with ether.…”
Section: Estimation Of Cyclic Amp Levelsmentioning
confidence: 99%
“…The cyclic AMP samples were lyophilized. The lyophilized samples were dissolved with sodium acetate buffer, pH 6.2, and they were used for the estimation of cyclic AMP and for calculating the recovery (15). The quantity of cyclic AMP was determined by a radioimmunoassay, using a commercial kit (Yamasa, Chiba).…”
Section: Estimation Of Cyclic Amp Levelsmentioning
confidence: 99%
“…In this work, we have attempted to characterize the mode of action of VIP on tracheobronchial smooth muscle by measuring VIP-mediated cyclic adenosine 3',5'-monophosphate (cyclic AMP) accumulation in this tissue. A number of agents stimulate the production of cyclic AMP, or inhibit its degradation, in the airways (Andersson, Bergh & Svedmyr, 1972;Inamasu, Shinjo, Iwasawa & Morita, 1974;Murad, 1974;Duncan, Griffin & Solomon, 1975;Ohkubo, Takayanagi & Takagi, 1976;Triner, Velliemoz & Verosky, 1977), and these actions may be related to their ability to produce bronchodilatation (Said et al, 1974;Andersson et al, 1972;Inamasu et al, 1974;Murad, 1974;Duncan et al, 1975;Ohkubo et al, 1976;Triner, et al, 1977). The bronchodilator action of VIP is of special interest in view of the recent demonstration that a VIP-like peptide occurs in normal lung tissue (Said & Mutt, 1977).…”
mentioning
confidence: 99%
“…These agents induce smooth muscle contraction by a process which appears to be associated with elevation in cGMP concentrations, however a direct causal relationship has not been established [6][7][8][9][10] and the biochemical link between the muscarinic receptor and guanylyl cyclase remains unknown [11][12][13][14][15][16][17]. We have previously shown that in isolated plasma membrane fractions from rat liver, muscarinic agents stimulate cGMP production, an effect that is inCorrespondence address: M. Alfonzo, Secci6n de Biomembranas, Instituto de Medicina Experimental, Cfitedras de Patologia General y Fisiopatologia, y Bioquimica, Facultad de Medicina, Universidad Central de Venezuela (UCV), Apartado 50587, Sabana Grande, Caracas, Venezuela hibited by atropine [18].…”
Section: Introductionmentioning
confidence: 99%